Students’ Perceptions of Simulation-Based Learning in Speech Pathology: A Pilot Study - Penman, Adriana; Hill, Anne E; Hewat, Sally; Scarinci, Nerina (International Journal of Practice-based Learning in Health and Social Care, 2020)
Due to increased student numbers and workforce limitations, speech pathology students have fewer opportunities to develop skills in working with adult populations in traditional clinical placements. Using simulation-based learning has proven to be advantageous in other disciplines. The use of simulation to develop clinical skills in speech pathology range of practice areas, including speech, language and swallowing in adults, has been less well researched. The aim of this study was to investigate students’ overall perceptions about simulation-based learning, particularly their confidence related to specific clinical skills and perceived anxiety about working with adult clients. Six final year speech pathology students enrolled in either a 4-year undergraduate or 2.5-year masters program participated in this research. Students engaged in five simulation-based learning activities across one day. Purposefully developed pre- and post- surveys were completed to explore students’ anxiety levels and perceptions of confidence regarding clinical skills across domains of foundation knowledge, case history, assessment, intervention, interaction and clinical reasoning, and anxiety levels. The Satisfaction with Simulation Experience (SSE) Scale was completed post-simulation experience. Students also participated in a focus group discussion following the simulation experience. Student median ratings of clinical skills improved from pre- to post-simulation across the six domains. All students reported that the simulation-based learning experience was valuable and reported increased levels of confidence and enhanced preparedness for their clinical placements. Findings from this study suggested that students value simulation-based learning and future research should explore learning outcomes from a longer, more intensive simulation program.